Tilapia Aquaculture (Oreochromis niloticus) by Using Minapadi System: Budidaya Ikan Nila (Oreochromis niloticus) Dengan Menggunakan Sistem Minapadi - Kristiana, Indra; Prama, Ega Aditya; Amir, Gusti Nu’man; Akbarurrasyid, Muhammad; Sofian, Achmad; Astiyani, Wahyu Puji; Sudinno, Dinno; Prajayati, Vini Taru Febriani; Pietoyo, Atiek; Tarigan, Rani Rehulina; Syah, Irvan Firman (Universitas Lancang Kuning, 2023)
High tilapia production indicates high demand,therefore it is necessary to produce tilapia in a sustainable manner. Sustainable tilapia production can be fulfilled through fish farming activities with various aquaculturemethods and systems. One of the integrated systems of tilapia aquaculturecan becarried out through minapadisystem.This community service activity (PKM) aims to increase the productivity of paddy fields so that they can be utilized for the production of agricultural products and for fish production through the minapadi aquaculturesystem in Karangkamulyan Hamlet, Cintakarya, Parigi, Pangandaran. The stages of this activity include: (i) planning and presentation of tilapia aquacultureusing the minapadi system; (ii) creating a minapadi system that integrates tilapia aquaculturewith rice; (iii) monitoring the growth of cultivated tilapia fish; and (iv) evaluation of activities related to the perceptions of the target community and the results of monitoring the growth of tilapia cultivated using the minapadi system. The results of monitoring fish growth obtained an absolute weight of 65,86 grams, while an absolute length of 7,86 cm and a specific growth rate of 3,84% per day. The results of monitoring water quality during maintenance were obtained, pH value 7 –7,9; temperature (26-34)oC and DO values (3,1 –11,3) mg/l. The results of monitoring and evaluation can be concluded that Cintakarya Village, which is included in the Parigi District, has the potential to develop tilapia aquaculturewith the minapadi system. This is shown by the enthusiasm of the cultivators while participating in PKM activities and being supported by natural resources that are suitable for the aquacultureof the minapadi system